2011
DOI: 10.1093/cercor/bhr322
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between Verbal Response Initiation and Suppression after Prefrontal Lesions

Abstract: Some of the most striking symptoms after prefrontal damage are reduction of behavioral initiation and inability to suppress automatic behaviors. However, the relation between these 2 symptoms and the location of the lesions that cause them are not well understood. This study investigates the cerebral correlates of initiation and suppression abilities assessed by the Hayling Sentence Completion Test, using the human lesion approach. Forty-five patients with focal brain lesions and 110 healthy matched controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 93 publications
5
38
0
2
Order By: Relevance
“…The findings of Robinson and colleagues raise the question as to whether the right lateral PFC might be part of an inhibition network requiring the concerted interaction of various brain regions for inhibition/suppression to occur. This notion is supported by previous findings from Volle et al (2012) and from our lab (Hornberger et al, 2011) highlighting the fact that orbitofrontal cortex lesions/atrophy are also strongly related to inhibition/suppression deficits on the Hayling test. These orbitofrontal changes might be related more to the prediction and evaluation of specific behavioural outcomes (Rudebeck and Murray, 2014), with patients unable to resist the prepotent response due to a failure to reevaluate their responses.…”
supporting
confidence: 87%
“…The findings of Robinson and colleagues raise the question as to whether the right lateral PFC might be part of an inhibition network requiring the concerted interaction of various brain regions for inhibition/suppression to occur. This notion is supported by previous findings from Volle et al (2012) and from our lab (Hornberger et al, 2011) highlighting the fact that orbitofrontal cortex lesions/atrophy are also strongly related to inhibition/suppression deficits on the Hayling test. These orbitofrontal changes might be related more to the prediction and evaluation of specific behavioural outcomes (Rudebeck and Murray, 2014), with patients unable to resist the prepotent response due to a failure to reevaluate their responses.…”
supporting
confidence: 87%
“…Deficits in the three different measures could doubly dissociate from each other but were unlikely to be due to differences in task format or stimuli. Later, Volle et al (2012) showed why this was the case: each of the three types of error was associated with lesions within different parts of PFC (see Figure 4). Figure 3).…”
Section: Dissociations Of Cognitive Symptoms Of Frontal Lobe Damagementioning
confidence: 99%
“…Previous neuropsychological research has consistently shown that patients with neuropsychiatric disorders and those with brain damage perform significantly worse on the HSCT than neurologically healthy individuals [31], [34], as do patients with narcolepsy [35]. The HSCT requires quick and accurate responses and activates brain areas that are dependent on language retrieval, semantic activation and selection in semantic search [36].…”
Section: Introductionmentioning
confidence: 99%